Role of E-Learning to meet the challenges in Higher Education Program - Arshi Naim (Scholars Digest Publishing, 2022)
This research aims to express how Learning Management Systems has facilitated effective learning and helped in overcoming the challenges that hurdled schooling in higher education in King Khalid University. Learning Management Systems has applied Blackboard for the applications of its E-learning services. This research was a pilot study completely based on secondary data that has been collected through King Khalid University Official Website www.kku.edu.sa and through the website of E-Learning Deanship. After the collection of data, researchers have evaluated the data validity though various methods to file result how blackboard has actually facilitated in overcoming challenges in higher education in KKU. Teachers who have been working for more than 7 years have been given in-depth interview to present their experience between phase before Blackboard and after, then their response were scaled on semantic differential. For meeting the strategic goals of KKU has not come without major challenges. Before the introduction of Blackboard University used to operate in separate campuses for male and female students and male instructors were not able to teach female students in face-to-face environments due to cultural hindrances and also different departments used studios where instructors gave lectures to female students who were watching through a television screen in the room next door. Female students were only permitted to ask questions through a telephone attached to the wall. Women also faced an additional challenge when it came to travelling to and from lectures. Another challenge was the huge geography and dispersion of campuses that was impacting instructor recruitment.
Keywords: E-Learning, Blackboard, whiteboard, face-to-face, virtual classrooms.